2015
DOI: 10.1371/journal.pone.0122478
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Stigma as a Determinant of Functioning in Young Adults with Narcolepsy

Abstract: Symptoms of narcolepsy tend to arise during adolescence or young adulthood, a formative time in human development during which people are usually completing their education and launching a career. Little is known about the impact of narcolepsy on the social aspects of health-related quality of life in young adults. The purpose of this study was to examine relationships between health-related stigma, mood (anxiety and depression) and daytime functioning in young adults with narcolepsy compared to those without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 48 publications
3
38
1
Order By: Relevance
“…physical activity programmes, Pilates, aqua aerobics, and relaxation) can help to improve insomnia, hypersomnia, and Total score of Oviedo Sleep Questionnaire and decrease the need for sleep aids . Some studies described an inverse relationship between hypersomnia and physical activity, with higher hypersomnia levels leading to reduced physical activity . This relationship was confirmed in our study; participants who incrementally increased their physical activity had reduced hypersomnia levels.…”
Section: Discussionsupporting
confidence: 89%
“…physical activity programmes, Pilates, aqua aerobics, and relaxation) can help to improve insomnia, hypersomnia, and Total score of Oviedo Sleep Questionnaire and decrease the need for sleep aids . Some studies described an inverse relationship between hypersomnia and physical activity, with higher hypersomnia levels leading to reduced physical activity . This relationship was confirmed in our study; participants who incrementally increased their physical activity had reduced hypersomnia levels.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Taft and Keefer (2016) found that the internalisation of stigma was associated with the highest levels of psychological distress and exacerbation of physical symptoms. Similar negative consequences of stigma have been found in young adults suffering from narcolepsy (Kapella, et al, 2015). Thus, our study expands this literature showing that chronic illness related stigma is a crucial element in the lives of students attending CFE because aspects of well-being such as general health and social functioning are affected.…”
Section: Discussionsupporting
confidence: 84%
“…It is important to note that various conceptualizations for what constitutes young adulthood exist [11,13], and several scholars agree that setting limits for developmental periods in terms of age range is somewhat arbitrary [13,14]. Following other researchers [15,16], we define young adulthood as extending from the late teens to the mid-thirties.…”
Section: Methodsmentioning
confidence: 99%